Sheer mischief - Mansell, Jill (Naperville, IL : Sourcebooks Landmark, 2017)
"It's not that Janey Sinclair isn't happy to see her sister--she just wishes that she could have arrived in a less dramatic fashion. Waking up at seven a.m. to Maxine waiting at the door wearing a borrowed wedding dress and with a police escort wasn't how Janey planned to start her Sunday. Still, life's never dull when Maxine's around, and Janey, who's rebuilding her life, is delighted that her sister's back in town. So when Maxine sets her sights on glamorous fashion photographer Guy Cassidy, Janey knows there's no limit to the mischief her sister will make in order to dispatch the competition. Little do they know that the competition is a lot closer to home than they think..."--
Keywords: Love stories